2018
DOI: 10.1002/jms.4069
|View full text |Cite
|
Sign up to set email alerts
|

Methyl group transfer upon gas phase decomposition of protonated methyl benzoate and similar compounds

Abstract: Gas phase decompositions of protonated methyl benzoate and its conjugates have been studied by using electrospray ionization-collision induced dissociation-tandem mass spectrometry. Loss of CO molecule, thus transfer of methyl group, has been observed. In order to better understand this process, the theoretical calculations have been performed. For methyl benzoate conjugates, it has been found that position of substituent affects the loss of CO molecule, not the electron donor/withdrawing properties of the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…It is well known that electron ionization mass spectra of 1,2-disubstituted aromatic compounds are substantially different from those of their positional isomers. There are a number of examples that in ESI conditions the ortho effect also takes place [25][26][27][28][29][30][31].…”
Section: Hplc-ms Analysismentioning
confidence: 99%
“…It is well known that electron ionization mass spectra of 1,2-disubstituted aromatic compounds are substantially different from those of their positional isomers. There are a number of examples that in ESI conditions the ortho effect also takes place [25][26][27][28][29][30][31].…”
Section: Hplc-ms Analysismentioning
confidence: 99%
“…It is worth mentioning that the ions at m/z 124 and 123 (Figures 1 and 2s-4s) observed for meta and para isomers are formed as a result of the loss of CO 2 molecule (process discussed in details previously 16 ).…”
Section: Dear Sirmentioning
confidence: 91%
“…It is worth adding that the product ion spectrum of [C 6 H 5 COOCD 3 +H] + has shown that the hydrogen atoms from methyl group are not directly involved in the hydrogen exchange. 16 It is also worth adding that the loss of water molecule from protonated benzoic acid is also accompanied by intramolecular hydrogen exchange as shown by the product ion spectra of respective deuterium-containing ions. 17 In this work, we decided to study the influence of substituents on the hydrogen exchange for methyl benzoates bearing different ring substituents.…”
Section: Dear Sirmentioning
confidence: 99%
See 2 more Smart Citations